The Relationship Between Social Engagement and Social Awareness Among Students in an Islamic Education Program - Khairunnikmah, Iffah; Nasir, Muhammad; Armella, Rega; Hasanah, Naomi Ainun (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
The globalization era with digital communication technology has led to a decline in social awareness within society. As agents of change, university students play an important role in building social concern through involvement in various activities. This research aims to examine the extent of influence that social activities have on the social awareness of Islamic Religious Education (PAI) students at UIN Sultan Aji Muhammad Idris Samarinda, who have demonstrated active participation in community service programs organized by HMPS PAI and the